Simultaneous enhancement of polymerization kinetics and properties of phthalonitrile using alumina fillers - Tay, Yu Shan (2023)
Alumina particles are investigated as a potential catalyst for phthalonitrile polymerization and as a property enhancer. In this work, extensive characterizations were conducted on alumina-filled resorcinol-based phthalonitrile to differentiate between the catalytic effect and the filler effect. Thermal gravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy suggest the occurrence of chemical interaction between alumina fillers and phthalonitrile, which provides an insight into the better performance of alumina-filled phthalonitrile resins. This hypothesis is further supported by the additional Al-N peak observed in the X-ray photoelectron spectroscopy (XPS) analysis when alumina is added to phthalonitrile before curing, as well as the presence of an exothermic peak in the differential scanning calorimetry (DSC) analysis that indicates the catalytic polymerization of phthalonitrile. This catalytic phenomenon observed by the addition of alumina fillers is beneficial for the improvement of the conventionally slow curing process of phthalonitrile and, more importantly, is coupled with observable enhancement of thermomechanical properties of the composite.